2019
DOI: 10.1111/cp.12184
|View full text |Cite
|
Sign up to set email alerts
|

Internet‐delivered parent–child interaction therapy: Two clinical case reports

Abstract: Background: Disruptive child behaviours can be the start of a trajectory towards poor psychological outcomes across the lifespan. Parent-child interaction therapy (PCIT) is an evidence-based intervention designed for treating disruptive behaviours in children aged 2-7 years. The program utilises live coaching during dyadic parent-child play sessions and preliminary evidence suggests that the program can be implemented using a video-teleconferencing format, thereby improving accessibility to families from rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Prior to the COVID-19 pandemic, internet-delivered PCIT (I-PCIT) was established as an efficacious treatment by Comer et al (2017). Notably, researchers have highlighted the use of I-PCIT to ameliorate transportation and geographic barriers to accessing mental health care for families living in rural areas (Kohlhoff et al, 2019). Garcia et al (2021) were the first to explore the effectiveness of I-PCIT during the pandemic.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…Prior to the COVID-19 pandemic, internet-delivered PCIT (I-PCIT) was established as an efficacious treatment by Comer et al (2017). Notably, researchers have highlighted the use of I-PCIT to ameliorate transportation and geographic barriers to accessing mental health care for families living in rural areas (Kohlhoff et al, 2019). Garcia et al (2021) were the first to explore the effectiveness of I-PCIT during the pandemic.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…Given the already small population sizes inherent in rural areas, compounded with the barriers to accessing care even when made available through telehealth, studying the effectiveness of teletherapy in rural areas can be challenging. Nevertheless, this has not prevented continued contributions including telephone (Dwight-Johnson et al, 2011; Heckman et al, 2018; Ransom et al, 2008) and videoconference (Gonzalez & Brossart, 2015; Griffiths et al, 2006; McCord et al, 2011) teletherapy interventions for a variety of populations such as veterans (Knowlton & Nelson, 2021; Morland et al, 2014) and children/families (Kohlhoff et al, 2020; Rooks-Ellis et al, 2020; Ryan et al, 2005) and presenting concerns such as depression (Openshaw et al, 2012; Ransom et al, 2008; Trombello et al, 2020; Tutty, 2008), psychosis (Lecomte et al, 2021), grief (Chang et al, 2016; Supiano et al, 2021), and substance use (Baca et al, 2007).…”
Section: Research Questionsmentioning
confidence: 99%
“…The caregiver receives in vivo coaching via either a bluetooth device directly connected to the visual interface (i.e., computer, tablet, or cell phone screen) or headphones connected separately to a cell phone. Studies comparing traditional inperson PCIT to iPCIT demonstrated promising results for iPCIT (Comer et al, 2017;Kohlhoff et al, 2019). Comer et al found that children who received iPCIT were more likely than those who received standard PCIT to be rated by evaluators masked to treatment condition to have an "excellent response" at posttreatment and the 6-month follow-up.…”
mentioning
confidence: 99%